2022
DOI: 10.1038/s41598-022-07677-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the volatile profile of microalgae and cyanobacteria using solid-phase microextraction followed by gas chromatography coupled to mass spectrometry

Abstract: Microalgae and microalgae-derived ingredients are one of the top trends in the food industry. However, consumers’ acceptance and purchase intention of a product will be largely affected by odour and flavour. Surprisingly, the scientific literature present a very limited number of studies on the volatile composition of microalgae and cyanobacteria. In order to fill the gap, the main objective of the present study was to elucidate the volatile composition of seven microalgal and cyanobacterial strains from marin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…These results agree with Coleman et al (2022) who refer 3,5-octadien-2one as one of the major compounds that contribute to the overall aroma of NO and TC and confer a mushroom/earthy smell. Moreover, previous studies related the seafood-like odor in microalgae to their high content of diketones, such as 3,5-octadien-2-one (Van Durme et al, 2013;Coleman et al, 2022;Moran et al, 2022). Similarly, our results also suggested that 3,5-octadien-2-one may have a major contribution to the aroma not only in the raw microalgae matrix but also in c and w NO samples, though in a milder way in the processed samples.…”
Section: Aroma-active Compounds In Microalgaesupporting
confidence: 78%
See 3 more Smart Citations
“…These results agree with Coleman et al (2022) who refer 3,5-octadien-2one as one of the major compounds that contribute to the overall aroma of NO and TC and confer a mushroom/earthy smell. Moreover, previous studies related the seafood-like odor in microalgae to their high content of diketones, such as 3,5-octadien-2-one (Van Durme et al, 2013;Coleman et al, 2022;Moran et al, 2022). Similarly, our results also suggested that 3,5-octadien-2-one may have a major contribution to the aroma not only in the raw microalgae matrix but also in c and w NO samples, though in a milder way in the processed samples.…”
Section: Aroma-active Compounds In Microalgaesupporting
confidence: 78%
“…In microalgae, alcohols are mainly formed as a result of secondary decomposition of hydroperoxides of fatty acids, except for branched alcohols which come from carbohydrates via glycolysis or from amino acids through the Ehrlich pathway (Giri et al, 2010). In contrast to other studies (Coleman et al, 2022;Moran et al, 2022), 1-octen-3-ol does not seem to have an impact on the overall aroma (Van Durme et al, 2013), although the isomer trans-2-octen-1-ol shows an effect. In the present study, 1,5-octadien-3-ol has high OAV for NO and TC, especially in the raw form.…”
Section: Aroma-active Compounds In Microalgaementioning
confidence: 68%
See 2 more Smart Citations
“…The analyses were performed on the axenic P. cordatum CCMP 1329 and xenic P. cordatum CCMP 1529 cultures, each with three biological replicates, as well as the respective medium control samples (Figure 1). The medium also proved to release volatiles, mostly hydrocarbons, which have been reported as algal constituents by others, but which are obviously contaminations [34,35], complicating the analyses. Nevertheless, due to the good chromatographic separation, compounds originating from the algae were clearly detectable because they were absent in the medium control.…”
Section: Volatile Analysismentioning
confidence: 93%